2019
DOI: 10.5430/afr.v8n1p103
|View full text |Cite
|
Sign up to set email alerts
|

Tax Revenue Effort in Nigeria

Abstract: Today, countries, especially the developing ones rebase their Gross Domestic Product (GDP) to determine their economic strength. Nigeria as an acclaimed giant in Africa cannot but continuously examine variables which may impact the economy. It is in this light that this study was intended to investigate the Determinants of Tax Revenue Effort in Nigeria. To achieve this, secondary data, as time series data, covering a period of 1980 to 2015, were used and sourced from the Central Bank of Nigeria Statistical Bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…So, this sector is positively contributing to the export of any economy which further leads the way to higher profits and income and boost tax revenues. Our results are consistent with the findings of Ikhatua and Ibadin (2019).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…So, this sector is positively contributing to the export of any economy which further leads the way to higher profits and income and boost tax revenues. Our results are consistent with the findings of Ikhatua and Ibadin (2019).…”
Section: Resultssupporting
confidence: 93%
“…Foreign trade contributes significantly in most developing economies via export duties, imports quotas, tariffs and so on. The outcome of this variable contradicts not just theory but also the findings of Gaalya, (2015); Brun and diakite (2016) and Ikhatua and Ibadin (2019).…”
Section: 𝑇𝐸 = 𝑇𝑅 𝑇𝑅 ⁄contrasting
confidence: 51%
See 1 more Smart Citation
“…However, tax revenue was more responsive to income level with a unit increase in income leading to 0.63 percent increment in tax revenue. In a similar study, Ikhatua and Ibadin (2019) showed that tax revenue is determined by agricultural sector productivity, manufacturing sector productivity, capital flight and trade openness using the autoregressive distributed lag model. Moreover, the study of Bassey and Efiong (2018) revealed that the inflation rate has a negative effect on tax revenue generation, while the degree of economic openness and the level of economic development are positively related with tax revenue in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the aforementioned can best be determined by a local spatial statistical technique such as the geographically weighted regression (GWR) that allows for the examination of spatial non-stationarity between tax revenue and its correlates. However, existing studies (see Ajide and Bankefa 2017;Akintoye et al 2019;Bassey and Effiong 2018;Ikhatua and Ibadin 2019;Muibi and Sinbo 2013a, b;Rabiu and Mustafa 2020;Taiwo 2016) on the determinants of government tax revenue have been largely limited to global modeling technique such as the ordinary least-squares (OLS) linear regression or spatial regression methods. The major assumption in a global model that has been regarded as fundamentally defective is that the relationship between the predictor and tax revenue are homogenous in space.…”
Section: Introductionmentioning
confidence: 99%